Kinetics of Iridium(III) Catalysed Oxidation of Butane 1:4-Diol with Alkaline Hexacyanoferrate(III) - Seth, S.K.; Goel, Anjali; Verma, G.R.; Singh, H.S. (Asian Journal of Chemistry, 2010)
Studies of the kinetics of iridium(III) chloride catalysed oxidation of butane-1 :4-diol by aqueous alkaline hexacyanoferrate(III) (HCF) were made at constant ionic strength. The results suggest the complex formation between iridium(III) species and the substrate anion. This complex with hexacyanoferrate(III) gives another complex which slowly decomposes into univalent Ir(I) species and the intermediate products which in turn are further oxidised by HCF(III) into the subsequent steps.